Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

A new Edgewood-Cathay Fauna from the Wulipo Bed (uppermost Ordovician to lowermost Silurian) in South China and its palaeoecological significance - Kai-Yan Shi; Bing Huang; Ren-Bin Zhan; Jia-Yu Rong (Palaeoworld, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Natural oligomeric iridoids - Shu-Xuan Wang; Ting-Zhu Ye; Shan-Rong Luo; Lie-Feng Ma; Zha-Jun Zhan (Phytochemistry, 2026)

A Quad-Polarimetric SAR image reconstruction network and wetland classification fusing optical texture and polarization information - Yating Zhan; Yujun Wang; Ke Song; Yiming Su; Xin Rong; Gui Zhou; Yefei Zhu; Ziqiao Xu (International Journal of Remote Sensing, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Rapid recovery of trilobites after the Late Ordovician mass extinction (LOME) - Xin Wei; Renbin Zhan; Jiayu Rong; Bing Huang; Guanzhou Yan (Earth-Science Reviews, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

How does urban green infrastructure influence tourist loyalty: A moderated mediation model - Liangliang Rong; Kehui Wu; Liangru Tao; Xiangyu Meng; Jiayi Feng; Lixia Peng; Zhongjian Fang; Guoqiang Zhan; Jian Wang (Journal of Outdoor Recreation and Tourism, 2026)

An octahedral CeO2 artificial interphase for dendrite-free and stable zinc-ion supercapacitors - Zhan Yang; Rong Liao; Sunwu Hu; Weiming Chen; Deliang Zeng; Zhuoyu Ji; Jia Hong Pan; Xiaolei Huang (Chemical Engineering Journal, 2026)

Density inversion method combining dense residuals and Bi-LSTM structure - Wei-jia Zong; Xing-jian Wang; Rong Qi; Yang Liu; Zhong-yue Luo; Zhan-bo Liu (Applied Geophysics, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

A nitrogen-rich covalent organic framework with high conductivity for high specific capacity Li-ion battery cathode - Xiaoning Zhan; Yucheng Jin; Rong Jiang; Dongdong Qi; Xiya Yang; Qi Zhang; Qingmei Xu; Zhixin Liu; Liancong Yue; Hailong Wang (Science Bulletin, 2026)

The binding of HIRRV phosphoprotein to TBK1 suppressed IRF3 phosphorylation to facilitate viral replication in HINAE cells - Feixiang Rong; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Coordinated horizontal transfer of multiple genes assembles a carotenoid biosynthesis pathway in aphids - Rong Hu; Jun Wu; Siying Li; Peiyu Yang; Gang Wu; Changying Niu; Shuai Zhan; Yazhou Chen (Insect Biochemistry and Molecular Biology, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Towards highly-reliable precise point positioning for maritime navigation - Zhen Gao; Rong Yang; Wenfeng Nie; Xingqun Zhan (Ocean Engineering, 2025)

Simulated analog crayfish meat based on 3D print: Effect of crayfish oil emulsion on gel properties of surimi - Xiaofeng Zhan; Shuhui Yang; Weixia Zhou; Yanyan Wang; Jianhua Rong; Youming Liu; Chuan Li; Yongqiang Zhao; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Biocontrol Effects and Potential Defence Mechanism of Bacillus velezensis JS6-1 Against Fusarium solani-Induced Postharvest Rots in Muskmelon - Yafang He; Jiayi Wei; Fushuang Chen; Ning Wang; Yajie Han; Zifei Wu; Xingwen Wang; Faqiang Zhan; Yingwu Shi; Rong Yang; Huifang Bao (Current Microbiology, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Ganodermanic acid, a new steroidal compound derived from the marine fungus Aspergillu s sp. ZJUT223 - Youmin Ying; Xiaoxiao Chen; Shijie Zhan; Si Yang; Jinli Liu; Weiguang Shan; Yuhao Lin; Rong Wang (Natural Product Research, 2025)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Application of molecular docking in sorption of hydrophobic organic contaminants on black carbon - Tian Liang; Nannan Wan; Yan-Rong Zou; Xuan Kou; Zhao-Wen Zhan; Ping'’an Peng (Science of The Total Environment, 2025)

Introduce multivariate two-dimensional information to establish a data-driven volume estimation model for complex microplastic fibers - Zhan-Ao Zhang; Rong Zhang; Rui Gan; Runqi Liu; Xuxiang Zhang; Yan Zhang (Science of The Total Environment, 2025)

The first set of Silurian marine red beds in South China: Spatiotemporal distribution, diachronism and paleogeographic significance - Xiaole Zhang; Jiayu Rong; Peng Tang; Renbin Zhan; Yi Wang; Zhongyang Chen; Ruiwen Zong; Bing Huang; Xin Wei (Science China Earth Sciences, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Optimization of moisture content and duration in low-speed rotational thermostatic tempering for enhanced physicochemical properties of indica rice flour - Rong Dong; Wenkang Luo; Xiwu Jia; Wenjing Huang; Jian Xia; Zhan Wang (Journal of Cereal Science, 2025)

Groundwater nitrate responses to extreme rainfall in alluvial–diluvial plain aquifers: Evidence from hydrogeochemistry and isotopes - Chu Wu; Hang Zhou; Chuiyu Lu; Yong Zhao; Rong Liu; Liwei Zhan; Zheming Shi (Journal of Contaminant Hydrology, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

The study of the response regularity of photosynthesis to flash drought in different vegetation ecosystems of the middle and lower reaches of the Yangtze River Basin - Yunjun Zhan; Chuanqi Ma; Yan Yan; Yongsi Luo; Xueting Wang; Senrong Wang; Yuejing Rong (International Journal of Biometeorology, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Experimental and numerical study of light, fragile vent covers under vented gas explosions - Baicheng Zhou; Xudong Zhi; Yuhuan Song; Zhan Li; Feng Fan; Rong Zhang (Engineering Structures, 2025)

New data on the Cambrian–Ordovician (Tremadocian) conodont biostratigraphy of Guizhou Province, Southwest China - Hadi Jahangir; Guan-Zhou Yan; Rong-Chang Wu; Ren-Bin Zhan (Palaeoworld, 2024)

Selective recovery of Au from waste printed circuit board by water-soluble organic leaching: The key role of in situ bromine mediation and identificationof pathway - Zhenfeng Xiong; Ying Huang; Yonghua Li; Changdong Sheng; Liwei Sun; Jing Ma; Baoyan Chi; Jiali Tan; Xiong Tang; Rong Zha; Xinhua Zhan (Journal of Hazardous Materials, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Synergistic adsorption and degradation of sulfonylurea herbicides by biochar-supported nano zero-valent iron composites in in-situ soil remediation - Wenwen Xie; Cheng Peng; Anqi Chen; Haoran Wang; Mabinty Sarah Tholley; Rong Qian; Sinan Lu; Wei Zhang; Xiuping Zhan (Chemical Engineering Journal, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Upcycling of waste disposable medical masks to high value-added gasoline fuel and surfactants products by sub/supercritical water degradation and partial oxidation - Fu-Rong Xiu; Longsheng Zhan; Yingying Qi; Tianbi Wu; Yawei Ju (Journal of Hazardous Materials, 2024)

Ca2+-nano starch-lutein endowed 3D printed surimi with antioxidation and mutual reinforcing transmembrane transport mechanisms via hepg2 and caco-2 cells model - Gaoshang Li; Rong Shi; Junqi Zhan; Yiduo Wu; Yue Wan; Qian Yao; Yaqin Hu; Chunhua Wu; Wenge Yang; Wubo Wan (Food Research International, 2024)

Evolution and deposition patterns of turbidity currents under complex vegetation canopies - Jiayi Li; Yantun Song; Chongfa Cai; Liwen Qiu; Rong Hao; Changhua Zhan; Qiong Yang (Journal of Hydrology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

Relationship between photochromism and persistent luminescence in barium-magnesium silicates - Rujun Yang; Long Chen; Cunjian Lin; Honghui Huang; Zishuang Wu; Chenhan Zhan; Yixi Zhuang; Rong-Jun Xie (Chemical Engineering Journal, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

A new cleistanthane diterpenoid from the cultures of a mutant of Calcarisporium arbuscula NRRL 3705 - Hui Lu; Hong-Yu Chen; Shan-Rong Luo; Lu Guo; Di Luo; Lie-Feng Ma; Zha-Jun Zhan (Phytochemistry Letters, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

H2O2-enhanced alkaline pretreatment and separation of tobacco stems for biocellulose composite films with potential application in food preservation - Danya Zhan; Qiongfen Yu; Ming Li; Zhenhua Gu; Shengnan Sun; Yinning Li; Aimin Li; Rong Zhu; Zhongfan Mo; Runfang Ma (Journal of Environmental Chemical Engineering, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

RTK ramp faults detection and exclusion by the hybrid control chart - Zhen Gao; Xingqun Zhan; Rong Yang (Advances in Space Research, 2024)

The response of crop yield, carbon sequestration, and global warming potential to straw and biochar applications: A meta-analysis - Rong Liu; Yiyun Hu; Xiangsheng Zhan; Jiawang Zhong; Peng Zhao; Hao Feng; Qin'ge Dong; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Synergetic treatment of waste tantalum capacitors and polyvinyl chloride by subcritical water: Tantalum recovery, benzoic acid production and dechlorination - Fu-Rong Xiu; Longsheng Zhan; Yingying Qi; Xinyue Lei; Jiali Wang; Haipeng Zhou; Wenting Shao (Process Safety and Environmental Protection, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Characterization of multi-band GNSS multipath in urban canyons using the 3D ray-tracing method - Shaoqian Li; Rong Yang; Xingqun Zhan (GPS Solutions, 2024)

INS-aiding information error modeling in GNSS/INS ultra-tight integration - Wei Gao; Xingqun Zhan; Rong Yang (GPS Solutions, 2024)

An alkali-enhanced subcritical water treatment strategy of short-chain chlorinated paraffins: Dechlorination and hydrocarbons recovery - Fu-Rong Xiu; Qingyun Bai; Yingying Qi; Xinyue Lei; Ruiqi Yang; Siyi Wang; Yixiao Wang; Jiali Wang; Longsheng Zhan; Haipeng Zhou; Wenting Shao (Science of The Total Environment, 2023)

Determination and petroleum geochemical significance of short-chain alkylbenzenes in lacustrine source rocks - Zhao-Wen Zhan; Guo-Xiang Wang; Yankuan Tian; Xin Zhan; Tian Liang; Yao-Ping Wang; Yan-Rong Zou; Ping'an Peng (Organic Geochemistry, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

An improved detection method of GNSS faults with fractional information divergence - Zhen Gao; Xingqun Zhan; Rong Yang (Advances in Space Research, 2023)

Elucidating the chemical structures of petroleum resin using solid-state 13C NMR - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Ping'’an Peng (Chemical Geology, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

High-efficiency promotion on dechlorination of polyvinyl chloride in subcritical water treatment by introducing waste concrete - Fu-Rong Xiu; Ruiqi Yang; Yingying Qi; Ke Zhou; Jiali Wang; Wenting Shao; Haipeng Zhou; Longsheng Zhan (Process Safety and Environmental Protection, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Injectable nano-composite hydrogels based on hyaluronic acid-chitosan derivatives for simultaneous photothermal-chemo therapy of cancer with anti-inflammatory capacity - Liduo Rong; Yao Liu; Yu Fan; Jing Xiao; Yanhong Su; Ligong Lu; Shaojun Peng; Weizhong Yuan; Meixiao Zhan (Carbohydrate Polymers, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Detrital zircon age signatures of the basal Cambrian sandstone unit in North China: implications for drainage divides during global Sauk transgression and separation from Gondwanaland - Rong-Hao Wei; Liang Duan; Xingliang Zhang; Qing-Ren Meng; Rong-Ruo Zhan; Chu-Xuan Ma; Jing Xu; Yi Shi; Xiao-Yin Zhang (International Geology Review, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

Electromagnetic monitoring with local mesh for time-lapse monitoring of hydraulic fracturing - Zihao Zhang; Jianxin Liu; Rongwen Guo; Kouao Laurent Kouadio; Shaoquan Zhan; Aiyong Li; Rong Liu (Journal of Applied Geophysics, 2023)

Experimental evaluation of a hybrid solar dryer with flexible open sorption thermal energy storage unit on demand for burdock root drying - Rong Zhu; Qiongfen Yu; Ming Li; Yiping Xia; Aimin Li; Danya Zhan; Yinning Li; Yunfeng Wang (Environmental Science and Pollution Research, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Research on type I kerogen molecular simulation and docking between kerogen and saturated hydrocarbon molecule during oil generation - Tian Liang; Zhao-Wen Zhan; Yan-Rong Zou; Xiao-Hui Lin; Yun Shan; Ping'’an Peng (Chemical Geology, 2023)

Correction: Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Design, synthesis, and antifungal activity evaluation of novel 2-cyano-5-oxopentanoic acid derivatives as potential succinate dehydrogenase inhibitors - Xue-song Wang; Xiao-rong Tang; Mi-jun Peng; Yong-zhan Mai (Medicinal Chemistry Research, 2022)

Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2021)

Interaction between β-lactam antibiotic and phosphorus-accumulating organisms - Rong Huang; Jing Lan; Chaoguo Zhan; Yanhui Ge; Lin Zhao (Environmental Science and Pollution Research, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

An Innovative Method to Evaluate Hydraulic Conductivity of a Single Rock Fracture Based on Geometric Characteristics - Jie Tan; Guan Rong; Hongbin Zhan; Renhui He; Song Sha; Bowen Li (Rock Mechanics and Rock Engineering, 2020)

A Density-Changing Centrifugation Method for Efficient Separation of Free Drugs from Drug-Loaded Particulate Delivery Systems - Lu Han; Hongyan Zhan; Xun Sun; Zhi-Rong Zhang; Li Deng (The AAPS Journal, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Origin and genetic family of Huhehu oil in the Hailar Basin, northeast China - Yao-Ping Wang; Fan Zhang; Yan-Rong Zou; Zhao-Wen Zhan; Yulan Cai (Acta Geochimica, 2018)

Transcriptional and translational responses of rapeseed leaves to red and blue lights at the rosette stage - Sheng-xin Chang; Chu Pu; Rong-zhan Guan; Min Pu; Zhi-gang Xu (Journal of Zhejiang University-SCIENCE B, 2018)

A deep water shelly fauna from the uppermost Ordovician in northwestern Hunan, South China and its paleoecological implications - Jiayu Rong; Xin Wei; Renbin Zhan; Yi Wang (Science China Earth Sciences, 2018)

Multi-type sensor placement and response reconstruction for building structures: Experimental investigations - Rong-Pan Hu; You-Lin Xu; Sheng Zhan (Earthquake Engineering and Engineering Vibration, 2018)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Fruit and vegetable consumption and risk of cardiovascular disease: A meta-analysis of prospective cohort studies - Jian Zhan; Yu-Jian Liu; Long-Biao Cai; Fang-Rong Xu; Tao Xie; Qi-Qiang He (Critical Reviews in Food Science and Nutrition, 2017)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Combination of Estrogen and Immunosuppressive Agents to Establish a Mouse Model of Candidiasis with Concurrent Oral and Vaginal Mucosal Infection - Le Wang; Chong Wang; Huan Mei; Yongnian Shen; Guixia Lv; Rong Zeng; Ping Zhan; Dongmei Li; Weida Liu (Mycopathologia, 2016)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

The Application of Laser Microdissection in Molecular Detection and Identification of Aspergillus fumigatus from Murine Model of Acute Invasive Pulmonary Aspergillosis - Chong Wang; Ping Zhan; Le Wang; Rong Zeng; Yongnian Shen; Guixia Lv; Dongmei Li; Shuwen Deng; Weida Liu (Mycopathologia, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Multi-parameter systematic strategy opinion that predicts, prevents, and personalized treats a cancer - Xianquan Zhan; Rong Hu; Xiaowei Wang (EPMA Journal, 2014)

Enhanced Oxidation Stability of Quasi Core-Shell Alloyed CdSeS Quantum Dots Prepared Through Aqueous Microwave Synthesis Technique - Hong-Ju Zhan; Pei-Jiang Zhou; Rong Ma; Xi-Jing Liu; Yu-Ning He; Chuan-Yun Zhou (Journal of Fluorescence, 2014)

Perceptual quality assessment of SAR image compression - Anzhou Hu; Rong Zhang; Dong Yin; Yuan Chen; Xin Zhan (International Journal of Remote Sensing, 2013)

Multi-parameter systematic strategies for predictive, preventive and personalised medicine in cancer - Rong Hu; Xiaowei Wang; Xianquan Zhan (EPMA Journal, 2013)
Cancer is a complex disease that causes the alterations in the levels of gene, RNA, protein and metabolite. With the development of genomics, transcriptomics, proteomics and metabolomic techniques, the characterisation of key mutations and molecular pathways responsible for tumour progression has led to the identification of a large number of potential targets. The increasing understanding of molecular carcinogenesis has begun to change paradigms in oncology from traditional single-factor strategy to multi-parameter systematic strategy. The therapeutic model of cancer has changed from adopting the general radiotherapy and chemotherapy to personalised strategy. The development of predictive, preventive and personalised medicine (PPPM) will allow prediction of response with substantially increased accuracy, stratification of particular patient groups and eventual personalisation of medicine. The PPPM will change the approach to tumour diseases from a systematic and comprehensive point of view in the future. Patients will be treated according to the specific molecular profiles that are found in the individual tumour tissue and preferentially with targeted substances, if available.

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

An overview of studies on psychological well-being in children born following assisted reproductive technologies - Qi-tao Zhan; Pei-pei Pan; Xiang-rong Xu; Hang-ying Lou; Yi-yun Lou; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

Improvement of the CuZn-superoxide dismutase enzyme activity and stability as a therapeutic agent by modification with polysialic acids - Jian Rong Wu; Yi Lin; Zhi Yong Zheng; Chi Chung Lin; Xiao Bei Zhan; Ying Qiang Shen (Biotechnology Letters, 2010)

Soil microbial properties under N and P additions in a semi-arid, sandy grassland - Lu-Jun Li; De-Hui Zeng; Zhan-Yuan Yu; Zhi-Ping Fan; Rong Mao (Biology and Fertility of Soils, 2010)

Expansion of the Cathaysian Oldland through the Ordovician-Silurian transition: Emerging evidence and possible dynamics - JiaYu Rong; RenBin Zhan; HongGen Xu; Bing Huang; GuoHua Yu (Science China Earth Sciences, 2010)

Research of the ATPase’s rotation catalysis stochastic transition dynamics - Yan Zheng; Ming-Jian Yang; Wei-Xia Wu; Kun Yu; Ying-Rong Han; Yong Zhan; Yan-Bin Huang (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

Numerical flow simulation in the post-endoscopic sinus surgery nasal cavity - Guanxia Xiong; Jiemin Zhan; Kejun Zuo; Jianfeng Li; Liangwan Rong; Geng Xu (Medical & Biological Engineering & Computing, 2008)

Sesquiterpenoid alkaloid from Acroptilon repens - Zha-Jun Zhan; Xiao-Rong Hou (Natural Product Research, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Characterization of Recombinant Human Cardiac KCNQ1/KCNE1 Channels (I Ks) Stably Expressed in HEK 293 Cells - Ming-Qing Dong; Chu-Pak Lau; Zhan Gao; Gea-Ny Tseng; Gui-Rong Li (The Journal of Membrane Biology, 2006)

Evaluation of caspase-dependent apoptosis during fluoride-induced liver lesion in pigs - Xiu An Zhan; Min Wang; Zi Rong Xu; Wei Fen Li; Jian Xin Li (Archives of Toxicology, 2006)